Pengembangan Karir dan Pemberian Reward sebagai Strategi Meningkatkan Kinerja Karyawan di PT Dwidaya Mira Persada - Vinda Sulvitri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In an increasingly competitive business environment, companies are required to continuously enhance employee productivity and performance to achieve their set targets. Employee performance reflects their level of satisfaction and responsibility toward their work, which directly impacts efficiency and outcomes. One strategic approach to improving performance is through career development programs designed to strengthen individuals' skills, attitudes, and character. Additionally, providing incentives in the form of rewards plays a crucial role in motivating employees to work more effectively. PT. Dwidaya Mitra Persada, a company engaged in heavy equipment rental and the provision of permanent employees (PKWTT), recognizes that effective human resource (HR) management is key to achieving optimal performance. Factors such as job performance, education level, and work tenure are fundamental components in the company’s career development initiatives. However, challenges such as low attendance rates and delays in task completion remain issues that need to be addressed. Therefore, prioritizing career development and implementing reward strategies are essential steps toward enhancing employee professionalism and ensuring the company's success.